2003
DOI: 10.7326/0003-4819-139-11-200312020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Bleeding in Patients Taking Oral Anticoagulant Therapy for Venous Thromboembolism

Abstract: The clinical impact of anticoagulant-related major bleeding in patients with venous thromboembolism is considerable, and clinicians should take this into account when deciding whether to continue long-term oral anticoagulant therapy in an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
426
1
23

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 704 publications
(476 citation statements)
references
References 63 publications
26
426
1
23
Order By: Relevance
“…Interestingly and despite the fact that XALIA was an observational study with less strict selection criteria than the phase 3 trials with DOACs, these incidences of major bleeding compare well to those observed in the RE‐COVER trials (0·54% and 1·0% per 6 months for dabigatran and warfarin, respectively) and HOKUSAI study (0·82% and 1·0% per 3–12 months for edoxaban and warfarin, respectively) (Schulman et al , 2009, 2014; Hokusai VTE Investigators 2013; Klok et al , 2016, 2017). Even so, considering the 1·1% incidence of major bleeding in the sensitivity analysis on warfarin treatment, the incidences of major bleeding in XALIA do seem representative in the perspective of the established yearly 2·7% incidence‐rate of major bleeding in patients on long‐term vitamin K antagonist treatment (Linkins et al , 2003). The strength of VTE‐BLEED in this ‘real‐world’ cohort of patients thus lies predominantly in the identification of the majority of patients with a very low risk of major bleeding, in whom anticoagulants could be continued safely beyond the first 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly and despite the fact that XALIA was an observational study with less strict selection criteria than the phase 3 trials with DOACs, these incidences of major bleeding compare well to those observed in the RE‐COVER trials (0·54% and 1·0% per 6 months for dabigatran and warfarin, respectively) and HOKUSAI study (0·82% and 1·0% per 3–12 months for edoxaban and warfarin, respectively) (Schulman et al , 2009, 2014; Hokusai VTE Investigators 2013; Klok et al , 2016, 2017). Even so, considering the 1·1% incidence of major bleeding in the sensitivity analysis on warfarin treatment, the incidences of major bleeding in XALIA do seem representative in the perspective of the established yearly 2·7% incidence‐rate of major bleeding in patients on long‐term vitamin K antagonist treatment (Linkins et al , 2003). The strength of VTE‐BLEED in this ‘real‐world’ cohort of patients thus lies predominantly in the identification of the majority of patients with a very low risk of major bleeding, in whom anticoagulants could be continued safely beyond the first 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…O principal risco da anticoagulação oral é a hemorragia 1,26,27 . Em nosso estudo, foram observados 15,4% (38,8 por 100 pacientes/ano) de eventos hemorrágicos nos 136 pacientes acompanhados, sendo a grande maioria destes de intensidade leve (13,2%) ou moderada (2,2%).…”
Section: Discussionunclassified
“…A incidência de complicações hemorrágicas não é homogênea na literatura 1,18,27 . Para o TEV, a incidên-cia de episódios de sangramento maior varia de 0,4 a 12,8%, sendo a maioria dos dados tirados de trabalhos prospectivos em que a warfarina foi comparada com diferentes tipos e regimes de heparinas de baixo peso molecular 18,27,28 .…”
Section: Discussionunclassified
See 2 more Smart Citations